Optimizing maritime logistics for sustainable development in Kenya's Blue Economy - Conrad Ochego Mogaka (Journal of Sustainable Development of Transport and Logistics)
Purpose: Kenya's strategic position on Africa's eastern coast makes its blue economy essential for national development. This study analyzes the relationship between sustainable maritime logistics and the potential of the blue economy to promote social equity, environmental sustainability, and economic growth. Methodology: A systematic literature review was conducted, synthesizing scholarly research, industry reports, and policy documents on maritime logistics and its contribution to Kenya's blue economy. The analysis focuses on key dimensions such as port infrastructure, regulatory frameworks, and technological innovation. Results: The study finds that efficient maritime logistics enhance trade efficiency, reduce transportation costs, and support sustainable practices, thus maximizing the blue economy's potential. However, challenges remain, including limited port capacity, inefficient customs processes, insufficient cold chain infrastructure, and gaps in workforce training. Addressing these issues requires policy reforms and investments in modern infrastructure. Theoretical Contribution: This research contributes to the sustainable development theory by positioning maritime logistics as a central element of blue economic resilience and environmental stewardship. It introduces a conceptual model viewing maritime logistics as an enabler of sustainable blue economy growth in Kenya. Practical Implications: The study recommends targeted investments in green technologies, improved maritime training, and the formation of multi-stakeholder partnerships to foster collaborative and resilient maritime logistics systems. It also highlights the need for more comprehensive data and encourages future research to include primary data for deeper insights.